Perjalanan Dakwah Rasulullah SAW dari Makkah ke Madinah - Sintia Yulianti; Jeski Maulana; Widia Wiska; Ega Nasyifa; Wismanto Wismanto; Fitria Mayasari (Reflection : Islamic Education Journal, 2025)
Prophet Muhammad SAW, was a religious leader and state leader who had a commendable personality. He is the best role model (uswatun hasanah) for Muslims throughout the Islamic world. Through the Islamiyah da'wah organization, the Prophet was able to change the course of history and greatly influence the development of Islamic broadcasting from the jahiliyah (pre-Islamic) era to the era of Islamic civilization. The mission of Rasulullah SAW during the Mecca to Medina period was aimed at forming a pluralistic Muslim personality (in Mecca) as an absolute element of building an Islamic government in Medina where the community of Medina residents was plural. Pluralism in Medina was reflected in the existence of differences in religion, ethnicity and class and to create tolerance between each other through the Islamic da'wah organization. The Prophet's success in building a government was marked by the creation of the Medina charter as a law that regulated the plural community of Medina residents. This was despite his efforts in fighting for and preaching Islam, so that he was known as a highly respected Messenger and received sympathy from Muslims in Mecca - Medina at that time and the Islamic world in general. This study aims to reveal the events of the Prophet Muhammad's migration, the factors that caused it, its impacts, and the lessons that contributed to the formation of Islamic society. The research method used in this research is the method This descriptive study uses literature as a data collection tool. The analysis used is data reduction, data presentation, and drawing conclusions. The results of this research show; (1) That in the da'wah journey there are strategies so that the da'wah conveyed can be accepted, (2) the importance of knowing the important elements in da'wah activities to describe the journey of the Prophet's da'wah according to Islamic history (Mecca - Medina period).